Brucellar arthritis: a study of 39 Peruvian families. Issue 7 (July 1987) - Gotuzzo, E; Seas, C; Guerra, J G; Carrillo, C; Bocanegra, T S; Calvo, A; Castañeda, O; Alarcón, G S
Abstract : A study was conducted to characterise the articular manifestation of Brucella melitensis within a family in Peru. From January 1981 to June 1986, 39 families with 232 individuals were evaluated. Brucellosis was diagnosed in 118 family members (attack rate of 50.9%). A lower attack rate was observed in children less than 10 years' old compared with other age groups (p less than 0.02). Complete clinical data were available in 92 of the 118 affected members. Moderate and severe forms of the diseases were more prevalent in women than in men (41.8% v 13.5%; p less than 0.001). Twenty eight of the 92 patients developed some brucellar complications; the articular involvement was the most prevalent (23.9%). Arthritis was also more common in women than in men (34.5% v 8.1%; p less than 0.01). Children appeared to have less articular involvement. Overall, the following pattern was observed: peripheral arthritis (54.5%); unilateral sacroiliitis (23.0%); mixed arthritis (4.5%), and spondylitis (9.1%). Spondylitis was seen only in the elderly with chronic brucellosis. Four patients developed extra-articular rheumatism. Within members of family groups, brucellar arthritis occurred less frequently than in individual patients from the same hospital. This suggests that many family cases were diagnosed in the early stages.